KOMPETENSI PENYULUH DALAM PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KOTA KENDARI - Rivan Rivan; Iskandar Zainuddin Rela; Salahuddin Salahuddin; Tjandra Buana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
The role of agricultural extension workers is very large in realizing food security for the Indonesian nation, so that the competence of an extension worker must always be improved in order to deal with increasingly diverse problems. This study aims to: find out the competence of extension workers in the use of information and communication technology in Kendari City. This research was conducted to all agricultural extension workers with status as civil servants and honorary workers in Kendari City. This research was conducted from May to July 2022 which is a quantitative study. Where the results of the study were analyzed using class intervals. The results showed that the competence of extension workers in the use of information and communication technology was in the high category, which was seen from the perceptions of extension workers in using computers, frequency of computer use, computer operation, outreach activities using computers, advantages of computers in extension activities, support for effective computer use, application software and the internet.